Evaluation the Solubility and the Porosity of the Nano Fast Cement Comparing to the Mineral Trioxide Aggregate:An in vitro Study - Fariborz Moazzami; Zahra Rajabzadeh; Habib Daneshmanesh; Yasmin Ghahramani (Shiraz University of Medical Sciences, 2023)
Statement of the Problem: New calcium silicate base cements are introduced as root repair materials in order to defeat the problems of early root repair materials. Their mechanical properties such as solubility and porosity should be concerned. Purpose: This study was conducted to evaluate the solubility and porosity of the NanoFastCement (NFC) as a new calcium silicate base cement comparing to mineral trioxide aggregate (MTA). Materials and Method: In this in vitro study, scanning electron microscope (SEM) was used to evaluate the porosity at five different magnifications (200×, 1000×, 4000×, 6000× and 10000×) in secondary backscattered electron mode. All analyses were performed at 20kV. The obtained images were subjected to qualitative evaluation regarding the porosity. Solubility was determined following the international standards organization (ISO) 6876 method. Twelve specimens in specially fabricated stainless steel ring molds were weighed, initially and after 24 hour and 28 days of immersion in distilled water. Each weight was measured three times to record the average weight. Solubility was measured by calculating the difference of the initial and final weight. Results: Solubility of the NFC in comparison with MTA showed no statistical difference (p Value > 0.05) after one day and 28 days. NFC acted like MTA and showed an acceptable solubility value at exposure time intervals. In both groups, solubility increased as time went on (p Value<0.05).The porosity of NFC was comparable to MTA, and NFC presented a less porous and a slightly smoother surface compared to MTA. Conclusion: NFC has similar solubility and porosity to Proroot MTA. Therefore, it can be a good, more available and less expensive substitute for MTA.